SPE International Symposium and Exhibition on Formation Damage Control 2008
DOI: 10.2118/112439-ms
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Aphron Fluid Technology for Completion and Workover Applications

Abstract: The literature describes several applications where Aphron fluid technology has been applied in both drilling and re-entry scenarios and includes an extensive description of how this fluid system works. A highly efficient leak-off prevention mechanism makes aphron based fluid systems beneficial for certain completion and workover applications as well, where formation damage could be avoided by the practical elimination of fluid-fluid or fluid-rock interaction or where simply the workover objectives can be achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It was Tom Brookey who first introduced aphron into petroleum industry for horizontal well drilling in 1998 [3] . After that successful field application, aphron had been widely used to redevelop the low pressure H 2 S gas carbonate formation in the Indian Basin Field of New Mexico, USA, in 2001 [4] , to control lost circulation while drilling highly fractured formation in California, USA, in 2001 [5] , to drill depleted reservoirs in Lake Maracaibo in 2002 [6,7,8] , to drill depleted formations in the North Sea 2003 [9] , to use as workover fluid in depleted mature fields in Tajin area of the Poza Rica in the Eastern Mexico 2003 [10] , to drill fractured granite formation in Yemen 2005 [11] and to complete and workover well in the cretaceous conglomerate sands of the deep basin region in Alberta, Canada, in 2008 [12] . Application results turn out that aphron based drilling fluid can be used to drill low-pressure reservoirs where UBD was unsuccessful.…”
Section: The Past Of Aphronmentioning
confidence: 99%
“…It was Tom Brookey who first introduced aphron into petroleum industry for horizontal well drilling in 1998 [3] . After that successful field application, aphron had been widely used to redevelop the low pressure H 2 S gas carbonate formation in the Indian Basin Field of New Mexico, USA, in 2001 [4] , to control lost circulation while drilling highly fractured formation in California, USA, in 2001 [5] , to drill depleted reservoirs in Lake Maracaibo in 2002 [6,7,8] , to drill depleted formations in the North Sea 2003 [9] , to use as workover fluid in depleted mature fields in Tajin area of the Poza Rica in the Eastern Mexico 2003 [10] , to drill fractured granite formation in Yemen 2005 [11] and to complete and workover well in the cretaceous conglomerate sands of the deep basin region in Alberta, Canada, in 2008 [12] . Application results turn out that aphron based drilling fluid can be used to drill low-pressure reservoirs where UBD was unsuccessful.…”
Section: The Past Of Aphronmentioning
confidence: 99%
“…However, it needs to be prepared under high‐speed agitation at about 10,000 r/min, which may be not easy to be achieved under the field condition. MacPhail et al researched on the application of aphron fluid and found that it can significantly prevent wellbore fluid loss and enable the well operation to be executed under dead well. Yet the foam is mainly used for the ultra‐low pressure oil and gas field.…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth and last applications, in a sisquoc sand well (unconsolidated permeable sand) aphron HYSST, drilling uid provided invasion control and avoided instability that might be encountered in sand wells. MacPhail et al [46] described several case studies of wells in Alberta and Mississippi. Aphron uid technology was successfully applied in several completion and workover applications leading to reduced uid loss.…”
Section: Introductionmentioning
confidence: 99%